2009
DOI: 10.1099/jmm.0.004531-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of Aspergillus endocarditis after cardiac surgery

Abstract: The prevalence of Aspergillus endocarditis (AE) is increasing in the hospital population. Aspergillus species contribute to approximately 25 % of all cases of fungal endocarditis. This study is a descriptive report of the use of nested PCR to detect DNA specific for Aspergillus species in serum for the diagnosis of cardiac infections. Open heart surgery was performed on patients and collected samples were examined microscopically and cultured. Ten sera in total from five patients were extracted for Aspergillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In immunocompromised patients, these methods may prove useful if the infection becomes systemic. There are many reports about molecular assays for the detection of systemic fungal infections using punfungal PCR with the available DNA primer sets for the recognition of all fungal species (35), nested PCR (36,37) and real time PCR (38)(39)(40). Molecular assays can serve as a valuable method for the diagnosis of FK in experimental animal infections and patients (41)(42)(43).…”
Section: Diagnosis Of Fungal Keratitismentioning
confidence: 99%
“…In immunocompromised patients, these methods may prove useful if the infection becomes systemic. There are many reports about molecular assays for the detection of systemic fungal infections using punfungal PCR with the available DNA primer sets for the recognition of all fungal species (35), nested PCR (36,37) and real time PCR (38)(39)(40). Molecular assays can serve as a valuable method for the diagnosis of FK in experimental animal infections and patients (41)(42)(43).…”
Section: Diagnosis Of Fungal Keratitismentioning
confidence: 99%
“…Few studies have reported on the BDG test in the pediatric population. Several PCR assays to detect Aspergillus DNA have been established [9,10], but few studies have been conducted on the molecular tools for the diagnosis of IA in children.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that early diagnosis of invasive Aspergillosis can be achieved through the detection of DNA in the samples [16]. The method is suitable for patients with severe underlying diseases because the samples can be obtained noninvasively and easily.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of FK has increased as a result of the frequent use of ocular corticosteroids and the rise in the number of patients who are immunocompromised, and comprises [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].9% of microbial keratitis [1,2]. Filamentous fungi are the major etiological agents of FK and Aspergillus species are the most common causes of the fungal infection worldwide, especially in tropical climates, reported as 24-30% in some studies [1,3].…”
Section: Introductionmentioning
confidence: 99%